Prinsip-Prinsip Pengelolaan Badan Usaha Milik Desa Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Ko’mara Kecamatan Polongbangkeng Utara Kabupaten Takalar - Samjulaifi, Samjulaifi; Muhammadiah, Muhammadiah; Usman, Djaelan (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the principles of management of village-owned enterprises and inhibiting factors and supporting factors of management of village-owned enterprises in improving the welfare of the community in Ko'mara Village, Polongbangkeng Utara District, Takalar Regency. This research used descriptive research with a qualitative approach. The number of informants in this study were 7 people. Data collection were interview, observation and documentation. Data analysis through data reduction, data review and conclusion , while the validity of the data used data triangulation, techniques and time. The results showed that the Ko'mara Jaya BUMDes programs which were still active included: savings and loans and the provision of iron tents could be said that with the establishment of BUMDes in the Ko'mara Village community was able to empower the community and be able to improve the welfare of the community and improve the economy community though not yet significant. Keywords: Management Principles, Village-Owned Enterprises